Analisis Kesalahan Ejaan Bahasa Indonesia di Ruang Publik Rumah Sakit Dian Harapan Tahun 2022: Analysis of Indonesian Language Spelling Errors in The Public Spaces at Dian Harapan Hospital in 2022 - Utami, Uma Fajar (Balai Bahasa Provinsi Papua, 2023)
Public space is a space or land owned by the public, a place for people to do activities, and a place to socialize. The use of the Indonesian language in public spaces is regulated in Law No. 24 of 2009 Article 38 that the Indonesian language must be used in public signs, road signs, public facilities, banners, and other information tools which are public services. This study aims to describe errors in the use of spelling and writing in foreign languages in the public spaces at Dian Harapan Hospital in 2022. This research uses descriptive qualitative methods that is to understand holistically phenomenon by using descriptions in the words and language's form. The data collection method used in the research are observation and documentation of photos and pictures taken from public spaces at Dian Harapan Hospital on August 2002. Based on the research on 50 photos/images of signs in the public space at Dian Harapan Hospital, 2 errors were found in the use of capital letters, 30 errors in writing abbreviations, 1 error in writing prepositions, 1 error in writing numbers, 4 errors in writing commas, 1 error in writing slash marks, and 12 errors in writing exclamation marks. The spelling errors in the public space at Dian Harapan Hospital occured due to a lack of knowledges about spelling rules (EYD V) and the absence of strict and real punishments on the errors and violations in using the language in the public spaces.